Challenges of international development projects in Yemen: Perspective of public work project / Hassan Mohammed Mohammed Lashuel - Hassan Mohammed, Mohammed Lashuel (2020)
International development projects are public projects that are created to support the economy and people’s life needs, mostly these types of projects target developing countries. These types of projects face challenges more than other projects due to many reasons. Accordingly, this research aims to explore the challenges that face international development projects in Yemen and conducted by the Public Work Project and highlight the most significant issues that face ID project as well to overcome these challenges. This research adopted the qualitative method by conducting ten semi-structured interviews with the PWP team and others stakeholders. The interview technique was selected to collect the data from the respondents from different backgrounds. Consequently, the data were analyzed using thematic analysis, which lead to creating themes for every group of respondents. Many challenges based on the PWP team were found as well as the other stakeholders. Based on the results, there are many challenges related to project management, personal interests and favoritism, delay, economy and security in the country, as well the issues related to contractors. For the highlighted challenges, recommendations from the respondents were developed, the long period of negotiation for the projects, should not be part of the project life cycle, additionally, the community should conscious of the benefits of development projects as well the other stakeholders. This research contributes significantly to improving the practice of the field of international development projects in Yemen as well as the other developing countries.